p38 MAPK plays an essential role in apoptosis induced by photoactivation of a novel ethylene glycol porphyrin derivative - Kralova, J; Dvorak, M; Koc, M; Kral, V (Oncogene, 2008)
In this study, we provide evidence that photostimulation of various cancer cells preloaded with a new photosensitizing compound, tetrakis-meso-(4-ethyleneglycol-2,3,5,6-tetrafluorophenyl) porphyrin (PORF-TEG), results in rapid activation of the cell death machinery. PORF-TEG, although primarily localized in lysosomes, induces mitochondria-driven apoptosis. The induction of apoptosis is accompanied by immediate and sustained activation of p38 mitogen-activated protein kinase (MAPK) and transient activation of c-Jun N-terminal kinase (JNK). Conversely, the inhibition of p38 by PD 169316 or SB202190 and by the p38alpha dominant-negative mutant as well as the deletion of the p38alpha gene (MEFs-KO) protected cells from apoptosis, whereas inhibition of JNK did not. Activation of the p38 signaling pathway occurs upstream of caspase activation. In addition, preincubation of cells with scavengers of reactive oxygen species attenuated p38 and caspase activation and increased cell survival, thus connecting reactive oxygen species formation with the activation of the p38 pathway. Later events included degradation of Bcl-2, activation of tBid, and cleavage of Bad and Mcl-1. The data suggest a key role for p38 MAPK in PORF-TEG-photoinduced apoptosis.
Keywords: Cell Line; nádorové buněčné linie; ethylenglykol; apoptóza; mitochondrie; porfyriny; Porphyrins; Light; reaktivní formy kyslíku; světlo; kaspasy; cytochromy c; Cell Line, Tumor; Caspases; Reactive Oxygen Species; Humans; mitogenem aktivované proteinkinasy p38; Mitochondria; Cytochromes c; buněčné linie; p38 Mitogen-Activated Protein Kinases; Ethylene Glycol; lidé; Apoptosis